Empirical evaluation of a preliminary model to identify low-risk MBA applicants - Bisschoff, Christo A. (Managing global transitions, 2012)
This article reports on the second stage of the model, namely to empirically evaluate the model's performance and validity across all three of the identified categories. These categories are 'Low-to-no risk' applicants for the MBA; and those applicants who did not complete the degree in 3 years, classified as 'Medium-to-low risk' applicants who are expected to complete their degree in extended study year, and 'High-risk' applicants who are not expected to complete their degrees and who drop out of the programme. The final-year MBA students at the PBS in 2004 and 2005 served as the research population. The results were very satisfactory. Concerning the categories Low-to-no risk and Medium-to-low risk applicants, the model can be used as predictive tool, presenting a validity higher than 60% (p = 0.9) and 90% (p= 0.7) respectively. Caution, however, looms at the category of High-risk applicants where the model judges too harshly with an error of 13.7% (p=0.7).
Keywords: MBA; napovedovalni model; predictive model; risk; tveganje; validity; veljavnost